Soluble tumor endothelial marker 1 in heart failure with reduced ejection fraction: A pilot study - Feng, Wen-Han; Chen, Po-Sheng; Chung, Hsing-Chun; Lin, Yi-Hsiung; Li, Yi-Heng (Frontiers in Cardiovascular Medicine, 2022)
Background Tumor endothelial marker 1 (TEM1/CD248) is a transmembrane protein that expresses in mesenchymal lineage derived cells during embryogenesis and becomes undetectable in normal adults after birth. Re-expression of TEM1 is found in organ fibrosis, wound healing and cardiac remodeling indicating its potential role in heart failure (HF). The purpose of this study is to explore the role of soluble TEM1 (sTEM1) in patients with HF with reduced ejection fraction. Methods We examined endomyocardial biopsy specimens from three HF patients and blood samples from 48 patients admitted for acute decompensated HF (age 72 years, men 61.7%). The expression of TEM1 in cardiac tissue and concentrations of sTEM1 in plasma were evaluated. Cultured rat cardiomyocytes (H9c2) and human cardiac fibroblasts (HCF) were stimulated with hypoxia or transforming growth factor beta (TGF-β) to observe the release of sTEM1 into culture media. The conditioned media of hypoxia-stimulated H9c2 cells was harvested and added into cultured cardiac fibroblast to evaluate its biological effect. Results Immunofluorescence study of biopsy specimens from three HF patients showed TEM1 expression in cardiomyocytes and cardiac fibroblasts. The plasma level of sTEM1 was significantly higher in patients (0.90 ± 0.23 vs. 0.33 ± 0.10 ng/mL, p = 0.032) with LVEF ≤ 35% compared with those with LVEF 36–49%. The sTEM1 levels had correlations with HF biomarkers of cardiac fibrosis, including growth differentiation factor-15 (GDF-15) and galectin-3. There was a significant increase in sTEM1 levels in the cultured media of H9c2 and HCF after being stressed with hypoxia or TGF-β. The conditioned media derived from hypoxia-stimulated H9c2 cells significantly increased cell proliferation of cardiac fibroblasts. This effect was partially reversed by anti-TEM1 antibody. Conclusion This pilot study demonstrated that cardiac TEM1 expression was upregulated in HF. The levels of sTEM1 were significantly higher in HF patients with LVEF ≤ 35% and correlated with other biomarkers of cardiac fibrosis. In vitro study proved that functional sTEM1 was released into cultured media after stressing cardiomyocytes and HCF.